The Problem Based Learning Model in Improving Concept Understanding and Self-Confidence Identification on Chemical Bonds at SMA Negeri 13 Pekanbaru - Hidayat, Helmy; Erna, Maria; Anwar, Lenny (Journal of Educational Sciences, 2021)
This study aims to see the improvement of conceptual understanding and identification of students self-confidence by applying the Problem Based Learning (PBL) learning model to chemical bonding material. This type of research is quantitative with a pre-experimental design using the one group pretest-posttest step. The sample of this research was 36 students of Class X MIA 1 at SMA Negeri 13 Pekanbaru. Data collection techniques were using questionnaires and questionnaires. Quantitative descriptive data analysis technique was by calculating the percentage value of students' concept understanding. The results of data analysis showed that there was an increase in understanding of the concept of chemical bonds from 37.28 (pretest) to 81.39 (posttest), which was an increase of 44.11. The results of the analysis using the paired sample t-test with a significance value of 0.000 < 0.05. The results of the identification of students self-confidence obtained 81.94 with a very good category. The application of the Problem Based Learning model can improve understanding of concepts and be able to raise the confidence of students.